Southern group of deepsthambhs - Banganga by Ghosh, Ayan (2023)
The deepsthambhs at the southern end of Banganga Tank are not only the largest in terms of their size, they are also unique in design, having influences from Goan temples. Those in the southeast corner have figures carved on them. Locals believe these deepstambhas are meant to be markers and they were built over the samadhis (burial places) of revered saints.